SCFAs-Induced GLP-1 Secretion Links the Regulation of Gut Microbiome on Hepatic Lipogenesis in Chickens - Zhang, Jian-Mei; Sun, Yin-Shuang; Zhao, Li-Qin; Chen, Tian-Tian; Fan, Mei-Na; Jiao, Hong-Chao; Zhao, Jing-Peng; Wang, Xiao-Juan; Li, Fu-Chang; Li, Hai-Fang; Lin, Hai (Frontiers in Microbiology, 2019)
The impact of gut microbiota and its metabolites on fat metabolism have been widely reported in human and animals. However, the critical mediators and the signal transductions are not well demonstrated. As ovipara, chicken represents a specific case in lipid metabolism that liver is the main site of lipid synthesis. The aim of this study is to elucidate the linkage of gut microbiota and fat synthesis in broiler chickens. The broilers were subjected to dietary treatments of combined probiotics (Animal bifidobacterium: 4 × 108 cfu/kg; Lactobacillus plantarum: 2 × 108 cfu/kg; Enterococcus faecalis: 2 × 108 cfu/kg; Clostridium butyrate: 2 × 108 cfu/kg, PB) and guar gum (1 g/kg, GG), respectively. Results showed that dietary supplementation of PB and GG changed the cecal microbiota diversity, altered short chain fatty acids (SCFAs) contents, and suppressed lipogenesis. In intestinal epithelial cells (IECs), SCFAs (acetate, propionate, and butyrate) up-regulated the expression of glucagon-like peptide-1 (GLP-1) via mitogen-activated protein kinase (MAPK) pathways, mainly via the phospho - extracellular regulated protein kinase (ERK) and phospho-p38 mitogen activated protein kinase (p38 MAPK) pathways. GLP-1 suppressed lipid accumulation in primary hepatocytes with the involvement of (AMP)-activated protein kinase/Acetyl CoA carboxylase (AMPK/ACC) signaling. In conclusion, the result suggests that SCFAs-induced GLP-1 secretion via MAPK pathway, which links the regulation of gut microbiota on hepatic lipogenesis in chickens.